STUDY AND ESTIMATION OF CATALASE ENZYME (CAT) LEVELS IN PATIENTS INFECTED WITH THE CORONAVIRUS USING THE ELISA TECHNIQUE - Tamara Nejres Ahmed; Fadam Muteb Abdoon Hamad; Kamaran Shukur Hussain (European Science Publishing, 2024)
Oxidative inhibitors encompass a wide range of entities that conduct an interruption process of the oxidation event employing free radical blockade or elimination. Thus, antioxidants' role is in constantly cleaning active oxygen and nitrogen species out of the organism by not giving them a chance to cause the destruction of living cells. The biochemical process catalyzed by Superoxide Dismutase and Catalase greatly limits oxygen free radicals. The viral infections do most easily develop due to the oxidative processes, as the oxygen free radicals aid virus reproduction. This study measured the level of CAT enzyme in the serum of 50 individuals infected with the coronavirus in two stages: the primary phase of disease (infection) and 10 days later, by way of ELISA device. The results indicate that there is a significant difference (P value < 0.01) between the enzyme concentrations in the studied groups when compared to the control group. Furthermore, the level of the enzyme CAT in the first stage group was lower compared to the second one. According to the study, coronavirus can boost the intracellular level of antioxidants which results in oxidative stress and thus, cellular damages.
Keywords: Antioxidants, CAT enzyme, Coronavirus, ELISA